Synthesis of 6-N-R-tetrazolo[1,5-c]quinazolin-5(6H)-ones and their anticancer activity - Antypenko, Oleksii; Kovalenko, Sergiy; Антипенко, Олексій Миколайович; Коваленко, Сергій Іванович (Acta Chimica Slovenica, 2016)
Chemical compounds with tetrazole ring are very interesting systems that can be valuable in pharmaceutical and clinical applications, especially as anticancer agents. In this work, novel 6-N-R-tetrazolo[1,5-c]quinazolin-5(6H)-ones were synthesized. A large set of IR, LC-, EI-MS, 1H, 13C NMR and elemental analysis data were collected and evaluated for their structures and purity. Details of synthesis, namely the N-alkylation, are discussed, including reactions with secondary and tertiary amides. Four new synthesized compounds (2.7, 3.2, 5.2, 5.3) were tested in vitro for anticancer activity at 10 μM against 60 cell lines of nine different cancer types: leukemia, melanoma, lung, colon, CNS, ovarian, renal, prostate, and breast cancers. Further synthesis of substances within the series of substituted tetrazolo[1,5-c]quinazoline systems will be attempted to develop improved compounds with better anticancer activity.
Keywords: Anticancer activity; 6-N-R-tetrazolo[1,5-c]quinazolin-5(6H)-ones; organic synthesis